In-Person or Virtual Study for International Students in the United States? - Martel, Mirka (International Higher Education, 2022)
Throughout the past two years, international students at US colleges and universities have grappled with what kind of educational experience they would be offered as part of their international exchange. This article provides an overview of two years of data regarding international students’ mode of study at US institutions and reflections on in-person and hybrid study in international educational exchange.